1998
DOI: 10.1200/jco.1998.16.4.1588
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and cancer pain: satisfaction and side effects with transdermal fentanyl versus oral morphine.

Abstract: These data suggest that patients are more satisfied with transdermal fentanyl compared with sustained-release oral forms of morphine. A lower frequency and reduced impact of side effects with transdermal fentanyl may be one reason cancer patients who receive fentanyl are more satisfied with their pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(119 citation statements)
references
References 9 publications
5
107
1
6
Order By: Relevance
“…• Improved patient acceptance and compliance (Payne et al 1998;Jarupanich et al 2003;Archer et al 2004). …”
Section: Active Methodsmentioning
confidence: 99%
“…• Improved patient acceptance and compliance (Payne et al 1998;Jarupanich et al 2003;Archer et al 2004). …”
Section: Active Methodsmentioning
confidence: 99%
“…Four controlled studies, however, found that transdermal fentanyl was associated with less frequent laxative use compared with morphine [19][20][21][22]. Tapentadol is a novel μ-opioid agonist that also inhibits norepinephrine, which is believed to augment its analgesic activity [23].…”
Section: Novel Opioids With Less Constipationmentioning
confidence: 99%
“…Large, randomized, controlled trials have not been done to directly compare opioids, and smaller individual trials are underpowered to demonstrate superiority of one opioid over another [14][15][16][17][18][19]. In addition, studies involving more recently available opioids have been undertaken in mainly noncancer populations.…”
Section: Evidence-based Rationale For Switching: Clinical Trialsmentioning
confidence: 99%
“…Drug company trials have focused on acute and/or nonmalignant pain [12,13], such as chronic back pain, and care should be taken when extrapolating data from those trials to support use in patients with cancer who, by nature, are less well and often taking multiple concomitant medications. To date, large RCTs have not been undertaken to directly compare opioids for cancer-related pain, and smaller individual trials are underpowered to demonstrate superiority of one opioid over another [14][15][16][17][18][19]. Therefore, www.TheOncologist.com the decision by both the WHO and the European Association for Palliative Care (EAPC) to recommend morphine as the opioid of choice is based largely on clinical expertise and pragmatic reasons, such as the general availability of morphine sulphate worldwide and the considerable clinical experience in using this drug.…”
Section: Evidence-based Rationale For Switching: Clinical Trialsmentioning
confidence: 99%